2021
DOI: 10.3389/fmed.2021.658259
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Macular Choroidal Thickness and Blood Flow Change by Optical Coherence Tomography Angiography After Posterior Scleral Reinforcement

Abstract: Purpose: This work aimed to study the effect of posterior scleral reinforcement (PSR) on choroidal thickness (CT) and blood flow.Methods: This study included 25 eyes of 24 patients with high myopia ( ≤ -6.0 dioptres or axial length ≥ 26.0 mm) who underwent PSR surgery. All patients completed the 1-month follow-up visit. Myopic macular degeneration (MMD) was graded according to the International Meta-Analysis for Pathologic Myopia (META-PM) classification based on color fundus photographs. Swept-source optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…5 ). This result was consistent with previous studies [ 9 , 29 ], reflecting that PSR can only improve short-term blood flow and had no long-term effect. Although the difference between experimental and control eyes was not statistically significant, we can speculate that scleral CXL has the same effect as PSR, both improving or maintaining blood flow in the posterior pole to a certain extent.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…5 ). This result was consistent with previous studies [ 9 , 29 ], reflecting that PSR can only improve short-term blood flow and had no long-term effect. Although the difference between experimental and control eyes was not statistically significant, we can speculate that scleral CXL has the same effect as PSR, both improving or maintaining blood flow in the posterior pole to a certain extent.…”
Section: Discussionsupporting
confidence: 94%
“…A scleral graft is placed over the macular area by insertion of the inferior oblique muscle, and the two ends of the graft are sutured to the superior and inferior nasal quadrants, wrapping the posterior pole. A recent study revealed that PSR may maintain the microcirculation of eyes with posterior staphyloma and thereby stabilize the best-corrected visual acuity [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the subjects were examined by SS-OCTA (SS-OCTA, VG200D, SVision Imaging, Ltd., China) (18), with the scanning mode 3 × 3 mm for FAZ measurement and to obtain the fundus images with the central area of 3 × 3 mm around the fovea of the macula. The data of 12 × 12 mm area centered on the fovea were obtained with 1,024 × 1,024 B-scans, 12 × 12 mm SS-OCTA images were captured with the commercial VG200 SS-OCTA device (19).…”
Section: Ss-octa Examinationmentioning
confidence: 99%
“…Zhang et al [ 38 ] found that both superficial and deep retinal blood flow density and blood flow index in the macular increased after PSR. Zhang et al [ 39 ] found that choroidal thickness and choroidal blood flow increased significantly after PSR in one week. Therefore, we might hypothesize that, due to the stimulating effect of the allograft sclera, neovascularization develops in the sclera, and the blood supply to the corresponding parts of the retina and choroid is improved, promoting metabolism in the optic cells, however, it remains to be proven.…”
Section: Discussionmentioning
confidence: 99%